2018
DOI: 10.1093/jhps/hny030
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular local infiltration analgesia in hip arthroscopy patients: a randomized, prospective study

Abstract: Hip arthroscopy patients can experience significant post-operative pain. Many strategies to combat this pain have been explored including nerve blocks, which can be costly. An alternative option for pain management is local infiltration analgesia (LIA) which has been studied in hip and knee arthroplasty, but its ability to decrease pain in the setting of hip arthroscopy remains uncertain. A prospective randomized controlled trial of 74 patients who underwent hip arthroscopy at a single medical center was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…As a result of the risks and limitations of lumbar plexus blockade, there is ongoing investigation of various administrative methods and pharmacologic cocktails to use in intra- or pericapsular injections. In a retrospective study, Philippi et al 13 found that patients receiving extracapsular local analgesia infiltration had lower requirement of rescue postoperative nerve blocks. Morgenthaler et al 11 found that patients receiving a postoperative intra-articular injection of 0.25% bupivacaine had lower postoperative pain while moving the operative limb, although pain at rest did not differ; as a result, the authors postulated that intra-articular injection may facilitate earlier, less painful range of motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the risks and limitations of lumbar plexus blockade, there is ongoing investigation of various administrative methods and pharmacologic cocktails to use in intra- or pericapsular injections. In a retrospective study, Philippi et al 13 found that patients receiving extracapsular local analgesia infiltration had lower requirement of rescue postoperative nerve blocks. Morgenthaler et al 11 found that patients receiving a postoperative intra-articular injection of 0.25% bupivacaine had lower postoperative pain while moving the operative limb, although pain at rest did not differ; as a result, the authors postulated that intra-articular injection may facilitate earlier, less painful range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Hip arthroscopy is commonly performed in the outpatient ambulatory surgical center setting; however, the optimal method to control pain while minimizing complications is not clear. 1,4,13,14,16,17,20 Most patients are discharged to return home from the postanesthesia care unit (PACU) on their day of surgery. Given the high levels of postoperative pain associated with hip arthroscopy, optimal analgesia is critical to ensure patient comfort and safety after discharge.…”
mentioning
confidence: 99%
“…Philippi et al 28 performed an RCT to investigate the efficacy of an extracapsular injection of 0.25% bupivacaine-epinephrine under direct arthroscopic visualization (n = 37) versus no injection (n = 37) after capsular repair during hip arthroscopic procedures. In the experimental cohort, after closure of the interportal capsulotomy, a spinal needle was arthroscopically placed into the extracapsular space, and 1:200,000 bupivacaine-epinephrine was injected.…”
Section: Resultsmentioning
confidence: 99%
“…Shlaifer et al 31 found that VAS pain scores were significantly lower in patients who received periacetabular bupivacaine injections as compared with intra-articular bupivacaine in the first postoperative 30 minutes and 18 hours. Philippi et al 28 reported that extracapsular bupivacaine-epinephrine injections resulted in significantly decreased maximum NRS scores in the PACU as compared with controls. Morgenthaler et al 23 demonstrated that those who received intra-articular bupivacaine injections had lower mean VAS pain scores over all time points between 30 minutes and 20 hours at rest as compared with placebo, but the differences were statistically significant at only the 30-minute postoperative time point.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated in patients undergoing cesarean section [143], knee replacement surgery [144], and laparoscopic cholecystectomy [145]. However, there are reported negative studies in patients undergoing hip arthroscopy [146] and knee replacement surgery [147].…”
Section: Surgical Wound Infiltrationmentioning
confidence: 99%